Enforcement of labor regulations in developing countries - Lucas Ronconi (IZA World of Labor, 2019)
More than half of private sector employees in the developing world do not receive legally mandated labor benefits. These regulations have typically been enacted by democratically elected governments, and are valued by both formal and informal workers. Increasing public enforcement (e.g. inspections, fines, and workers' access to the judiciary) can be a powerful tool to reduce violations (e.g. increase the number of employees earning above the minimum wage). Which factors determine enforcement, and whether enforcement produces more social benefits than costs, are, however, unanswered questions.
Keywords: E26; J46; 330; self-employment; poverty; labor earnings